2021
DOI: 10.3390/jcm10235524
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Video-Laryngoscopy versus Direct Laryngoscopy for Double-Lumen Endotracheal Intubation: A Systematic Review and Meta-Analysis

Abstract: The available meta-analyses have inconclusively indicated the advantages of video-laryngoscopy (VL) in different clinical situations; therefore, we conducted a systematic review and meta-analysis to determine efficacy outcomes such as successful first attempt or time to perform endotracheal intubation as well as adverse events of VL vs. direct laryngoscopes (DL) for double-lumen intubation. First intubation attempt success rate was 87.9% for VL and 84.5% for DL (OR = 1.64; 95% CI: 0.95 to 2.86; I2 = 61%; p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The clinical role of VL on tracheal intubation with double-lumen endobronchial tube (DLEB tube) for thoracic surgeries has been reviewed [172,173]. For tracheal intubation with double-lumen endobronchial tube, VL was found either to be superior or equivalent to DL [174][175][176][177][178][179].…”
Section: Double-lumen Endobronchial Tubementioning
confidence: 99%
“…The clinical role of VL on tracheal intubation with double-lumen endobronchial tube (DLEB tube) for thoracic surgeries has been reviewed [172,173]. For tracheal intubation with double-lumen endobronchial tube, VL was found either to be superior or equivalent to DL [174][175][176][177][178][179].…”
Section: Double-lumen Endobronchial Tubementioning
confidence: 99%
“…Video laryngoscope-assisted DLT intubation has been proved to be superior over traditional direct laryngoscope in terms of the intubation time and glottic view in multiple studies [ 14 ]. Not only the assisting tools that have been developed but DLT itself could be equipped with a video system, and this consequently reduces the need for fiberoptic bronchoscopy [ 15 ], with which the intubation time could be shortened and the success rate could be improved for senior anesthesiologists in a manikin model [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 10 , 18 ] However, some researchers reported that video laryngoscopes require a longer or shorter intubation time than the Macintosh laryngoscope. [ 12 , 19 , 20 ] This heterogeneity of previous findings might be explained by different definitions of the intubation time, type of video laryngoscope, and operators’ experience. [ 18 , 19 ] A previous meta-analysis indicated that novice operators may require more time to perform DLT intubation with video laryngoscopes than with the Macintosh laryngoscope.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 , 19 , 20 ] This heterogeneity of previous findings might be explained by different definitions of the intubation time, type of video laryngoscope, and operators’ experience. [ 18 , 19 ] A previous meta-analysis indicated that novice operators may require more time to perform DLT intubation with video laryngoscopes than with the Macintosh laryngoscope. [ 18 ] In this study, a single experienced anesthesiologist performed intubation, and the intubation time was defined as passage of the intubation device through the lips to connect the DLT and a circuit of anesthesia workstation to measure the time taken only for the intubation technique.…”
Section: Discussionmentioning
confidence: 99%